Harnessing heterogeneous nucleation to control tin orientations in electronic interconnections - Z. L. Ma (Nature Portfolio, 2017)
Control over the crystallographic orientation of solder joints based on βSn will improve the reliability of electronic interconnects. Using a technique based on droplet solidification and lattice matching, Ma et al. are able to control the βSn nucleation events, hence control the grain orientation.